PROTECTIVE EFFECTS OF CISTANCHES HERBA AQUEOUS EXTRACT ON CISPLATIN-INDUCED PREMATURE OVARIAN FAILURE IN MICE - Pan, Pengyu; Wang, Ying; Leng, Xue; Deng, Jinfang; Wang, Chun (African Journal of Traditional, Complementary and Alternative Medicines, 2017)
Background: Chemotherapeutic treatment of premenopausal women has been linked to premature ovarian failure (POF). Cistanches Herba (CH) is a commonly used male impotence and female infertility treatment in China; however, whether CH protects ovaries from chemotherapeutic drug-induced POF remains unclear. In this study, we investigated the protective effects of CH in a mouse model of chemotherapeutic drug-induced POF.Materials and Methods: We administered low- and high-concentration CH to cisplatin-induced POF mice for 2 weeks and determined body and ovarian weights, as well as serum follicle-stimulating hormone (FSH) and estradiol concentrations, to evaluate ovarian function. In addition, we evaluated the protective mechanisms of CH by detecting the levels of apoptosis-related proteins and evaluating markers of mitochondrial function.Results: In POF mice, we observed reduced body and ovarian weights; elevated serum FSH and attenuated estradiol concentrations; apoptosis of ovarian granulosa with concomitant changes in apoptosis-related proteins (including caspase-3, poly adenosine diphosphate-ribose polymerase, Bcl-2, and Bax); and mitochondrial dysfunction, such as a reduction in mitochondrial numbers, destruction of ultrastructural morphology, decrease in ATPase activity, and decreases in mitochondrial membrane potential and mitofusin-2 (a mitochondria dynamin-like GTPase). Significantly, CH reversed, to an extent, functional and morphologic injuries and ovarian tissue apoptosis by up-regulating the level of Mfn2 and the ratio of Bcl-2/Bax. Furthermore, CH reduced cisplatin-induced mitochondrial dysfunction in ovarian tissues.Conclusion: The present findings showed that CH inhibited cisplatin-induced POF through interactions between Mfn2 and Bcl-2/Bax proteins and, possibly, by up-regulation of Mfn2 expression. Ultimately, CH protects ovarian tissues from cisplatin-induced apoptosis.